Impact of Money Supply on Inflation Rate in Egypt: A VECM Approach - Dekkiche Djamal (Economics and Business)
In this work, the research team employed a VECM regression model to evaluate the relationship between money supply and inflation rate (INF) in Egypt from 1990 to 2019. The model includes four independent variables: money supply (MS), imports (IMP), Gross Domestic Product (GDP), and exchange rate (EXCH). A Johansen-Juselius co-integration test and a Vector Error Correction Model were used to determine the existence of long-term and short-term links between the variables. The results demonstrated the existence of co-integrating links between the variables. Aside from the effects of GDP, all independent factors had a positive effect on the inflation rate. Depending on the results, the money supply is the primary long-term predictor of the inflation rate in Egypt.